Coagulation and advanced oxidation in the removal of contaminants and antibiotic resistance in domestic wastewater (Research, Society and Development, 2025)
The effluent water from oxidation lagoons in Calceta, Ecuador, was evaluated, along with its subsequent treatment through advanced oxidation. The objective was to assess the efficiency of zeolite as a catalyst in the advanced oxidation process to mitigate antibiotic-resistant bacteria in domestic wastewater. The physicochemical parameters of the effluent from the oxidation lagoon were characterized before and after the treatments, including pH, turbidity, total solids (TS), suspended solids (SS), and electrical conductivity (EC). Fifteen advanced oxidation treatments were applied, varying the ozonation times and the doses of zeolite and hydrogen peroxide (H₂O₂). The results showed that treatments with ozone and H₂O₂, combined with zeolite, achieved a significant reduction in contaminants. A reduction of 99,99% in total coliform growth was reached. The treatments were also effective in the removal of color (up to 92,59%) and the reduction of turbidity (up to 93,06%). Despite these results, the isolated microorganisms were resistant to bacitracin and ampicillin but showed sensitivity to amikacin and levofloxacin, with inhibition zones reaching 34 mm.